The Romanian Economic Reform Program - Demekas, Dimitri (IMF Working Papers; Working Paper ;, 1991)
With the start of the process of its transition to a market economy in early 1990, Romania joined the ranks of other reforming Eastern European countries. At the starting point of its reform program, however, Romania was in a deep economic and institutional crisis and had no experience in even modest attempts to reform its economy. This paper outlines the main characteristics of the Romanian economic system before the reform, and presents the evolution of the reform program, as well as its achievements in the first year or so since it was launched.